FUNDAMENTAL STUDIES ON BEACH EROSION - Sawaragi, Toru (Doboku Gakkai ronbunshū, 1963)
So far, the systematic studies on beach process have been scarcely developed, and the establishment of the mechanics of beach process have been left as unknown field because of the complication of its mechanism. The author has made an effort to clarify this subject for many years, and published some of the results of studies in the Proceedings of the Conferences on Coastal Engineering in Japan and the Annuals of the Disaster Prevention Research Institute, Kyoto University. In this paper, the summary and conclusions of the studies on this subject by the author are presented with the following items : 1. Fundamental studies on the dynamic process of beach erosion by the sand movement in the parpendicular direction to a shoreline. 2. Fundamental studies on the dynamic process of beach erosion by littoral sand drifts. 3. Applied studies on the dynamic process of beach erosion by coastal structures. 4. Similitude on model experiments on moving bed.